2005
DOI: 10.1080/01443610500231450
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of intravaginal misoprostol and intracervical Foley catheter for cervical ripening and induction of labour

Abstract: Induction of labour may be indicated despite an unripe cervix. The purpose of this study was to compare the safety and efficacy of intravaginal misoprostol and an intracervical Foley's balloon catheter for preinduction cervical ripening and labour induction. A total of 120 patients requiring indicated induction of labour with an unfavourable cervix (Bishop's score < or =4) were randomised prospectively to receive either 50 mug intravaginal misoprostol every 6 h for a maximum of two doses, or an intracervical F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
6
23
2
2
Order By: Relevance
“…Another later review 30 documented the superiority of the catheter over PGE 2 and showed the catheter to have the same efficacy as application of PGE 1 while causing fewer abnormalities in contractions. In contrast to our observations, another recent study 31 concluded that a 50 microgram dose of misoprostol is more effective than a balloon catheter in inducing labour, with the same degree of safety.…”
Section: Discussioncontrasting
confidence: 56%
“…Another later review 30 documented the superiority of the catheter over PGE 2 and showed the catheter to have the same efficacy as application of PGE 1 while causing fewer abnormalities in contractions. In contrast to our observations, another recent study 31 concluded that a 50 microgram dose of misoprostol is more effective than a balloon catheter in inducing labour, with the same degree of safety.…”
Section: Discussioncontrasting
confidence: 56%
“…e induction delivery interval of 6.89 ± 0.89 versus 8.63 ± 1.18 hours was signi cantly greater for subjects in group 2 in this study and was similar to the ndings of Owolabi in Ile-Ife [12], Nigeria, who reported similarly signi cantly increased induction delivery interval in the Foley catheter group.…”
Section: Discussionsupporting
confidence: 77%
“…[11][12][13][14][15][16][17][18][19] The details of our search can be found in Figure 1. The studies' details are summarised in Table 1, and their quality assessment is detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%